Experimental Hematology & Oncology - Li, Zihai; Hsueh, Chung-Tsen; Liu, Delong; Wu, Kongming
Experimental Hematology & Oncology is an open access journal that encompasses all aspects of hematology and oncology with an emphasis on preclinical, basic, patient-oriented and translational research. The journal acts as an international platform for sharing laboratory findings in these areas and makes a deliberate effort to publish clinical trials with 'negative' results and basic science studies with provocative findings. Experimental Hematology & Oncology publishes original work, hypothesis, commentaries and timely reviews. With open access and rapid turnaround time from submission to publication, the journal strives to be a hub for disseminating new knowledge and discussing controversial topics for both basic scientists and busy clinicians in the closely related fields of hematology and oncology.